Sequential Enzymatic and Mild-Acid Hydrolysis of By-Product of Carrageenan Process from Kappaphycus alvarezii - Paz-Cedeno, Fernando Roberto [UNESP]; Solórzano-Chávez, Eddyn Gabriel [UNESP]; de Oliveira, Levi Ezequiel; Gelli, Valéria Cress; Monti, Rubens [UNESP]; de Oliveira, Samuel Conceição [UNESP]; Masarin, Fernando [UNESP] (Springer Nature, 2019)
Kappaphycus alvarezii is a red macroalgae widely used to produce carrageenan. The carrageenan processing produces a by-product rich in glucan which has been reported as easily hydrolyzed with enzymes, but the hydrolysate forms a gel at usual fermentation temperatures. The purpose of this study was to evaluate the enzymatic hydrolysis integrated with a mild-acid treatment of the by-product to obtain a hydrolysate rich in monomeric sugars. Using an enzyme load of 10 FPU g−1 of by-product, close to 100 and 14.7% of glucan and galactan conversion were reached, respectively. Increasing the enzyme load to 100 FPU g−1 raised the galactan conversion to 30%. The mild-acid treatment after enzymatic hydrolysis was satisfactory, increasing the glucose and galactose concentrations, without producing significant amounts of fermentation inhibitors and avoiding the formation of a gel structure. The statistical analysis showed that the main effects on the response were negative for the three independent variables, meaning that the selectivity (S) becomes lower when experimental conditions at the higher levels are used (longer time, higher temperature, and acid concentration). Therefore, the integrated enzymatic and acid hydrolysis of the by-product becomes a promising technological route to produce monomeric sugars for bioethanol or fine chemical production.
Keywords: By-product; Carrageenan; Chemical composition; Enzymatic and acid hydrolysis; Kappaphycus alvarezii